Suicidality, resilience and burnout in a population of oncology nurses - Milena M. Despotović; Dragana Ignjatović Ristić; Dragić Banković; Dragan Milovanović; Željko Stepanović; Mile Despotović; Milena Zlatanović; Diana Raketić; Milan Milisavljević; Jelena Boljanović; Mila Ćetković (Scientific Reports)
Abstract Oncology care gives employees the opportunity to care for people during the most difficult periods of their lives, which can affect the psychological well-being of nurses in different domains. The aim of this work is to examine is suicidality connected with resilience and burnout in the populations of oncology and non-oncology nurses, nursing students and administrative workers, as well as to determine if oncology nurses differ from other groups. The study included a total of 75 oncology nurses, 74 non-oncology nurses, 71 administrative workers and 70 nursing students. The respondents filled out the Serbian version of the Risk Assessment Suicidality Scale, the Serbian version of the Brief Resilience Scale, and the Maslach Burnout Inventory. The observed variables were compared by Spearman’s Rho correlation. In the population of oncology nurses, resilience and suicidality are negatively correlated (r = − 0.375, p = 0.001). In the same population, suicidality and burnout are not correlated, but the correlation was significant in all other control groups. Our research established the importance of strengthening the resilience of employees in the health sector, through various programs and trainings. Working professionals are more often forced to develop individual protective strategies and incorporate them into daily practice.